MOVIES: THE AESTHETIC INTERDISCIPLINARY DEVICE BRIDGING THE DIVERSITY GAP - Lu, Lucia Y. (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
In the course of Exploring Social and Cultural Perspectives on Diversity, a course required for all students of education major, to enhance the teaching of the concepts of multicultural education, and the differentiation of culturally responsive strategies, the author as teacher educator and her students as teacher candidates supplement movies in this course conceptualizing pragmatics, semiotics and aesthetics into literacy education by inviting students of diversity to watch movies, talk about movies, write movies, and act movies. Pragmatics is the study of how language is used for communication in various social and cultural contexts; semiotics is the study of signs like languages, arts, music, dance, drama, films, and paralinguistics which includes the nonverbal communication signals, etc., that human created to mediate the world; and aesthetics is the artistic stance that learners take for responses to literacy experiences. The purposes of this study are multi-functional: to develop the multisensory acquisition of five literacy skills in thinking, listening, speaking, writing and reading in a pleasant and authentic discourse setting. Both students from diversity and mainstream cultures acquire natural language for social interaction. Based on research, most students from diversity need two years to develop the social language, while needing five years to obtain the academic language. The results from this research reveal that audio-visual approach in terms of movies fosters students’ cultural awareness, expedites English as second language acquisition for social function toward academic success and globalization.